Temporal features of adult neurogenesis: differences and similarities across mammalian species - Levy, Frederic; Keller, Matthieu; Brus, Maïna (Frontiers in Neuroscience, 2013)
Production of new neurons continues throughout life in most invertebrates and vertebrates like crustaceans, fishes, reptiles, birds, and mammals including humans. Most studies have been carried out on rodent models and demonstrated that adult neurogenesis is located mainly in two structures, the dentate gyrus (DG) of the hippocampus and the sub-ventricular zone (SVZ). If adult neurogenesis is well preserved throughout evolution, yet there are however some features which differ between species. The present review proposes to target similarities and differences in the mechanism of mammalian adult neurogenesis by comparing selected species including humans. We will highlight the cellular composition and morphological organization of the SVZ in primates which differs from that of rodents and may be of functional relevance. We will particularly focus on the dynamic of neuronal maturation in rodents, primates and humans but also in sheep which appears to be an interesting model due to its similarities with the primate brain.